Public Affairs and Administration 2015
DOI: 10.4018/978-1-4666-8358-7.ch041
|View full text |Cite
|
Sign up to set email alerts
|

Industry-Led Standardization as Private Governance?

Abstract: Industry-led technical standardization is often cited as an example for private governance. And the Digital Video Broadcasting (DVB) Project is often presented as a particularly successful case of such governance without government. The successes of the industry-led DVB Project have often been cited as evidence for the superior governance capacity of private industry. While the commercial and engineering success of the DVB Project is unequivocal, this chapter raises the question whether it has been equally suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Our findings advance understanding of the nuances of standard-setting systems in some developed economies. For example, prior studies have suggested that governments are actively involved in standard setting in Germany, France, and other European countries (Blind et al, 2017; Borraz, 2007; Meyer, 2012). However, it remains unclear how firms respond to government influence in standard setting there and what mechanisms drive such responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings advance understanding of the nuances of standard-setting systems in some developed economies. For example, prior studies have suggested that governments are actively involved in standard setting in Germany, France, and other European countries (Blind et al, 2017; Borraz, 2007; Meyer, 2012). However, it remains unclear how firms respond to government influence in standard setting there and what mechanisms drive such responses.…”
Section: Discussionmentioning
confidence: 99%